2008
DOI: 10.2478/s11658-008-0005-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the DNA binding element of the human ZNF300 protein

Abstract: The human ZNF300 gene is a member of the KRAB/C2H2 zinc finger gene family, the members of which are known to be involved in various developmental and pathological processes. Here, we show that the ZNF300 gene encodes a 68-kDa nuclear protein that binds DNA in a sequence-specific manner. The ZNF300 DNA binding site, C(t/a)GGGGG(c/g)G, was defined via a random oligonucleotide selection assay, and the DNA binding site was further confirmed by electrophoretic mobility shift assays. A potential ZNF300 binding site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 18 publications
(21 reference statements)
0
21
0
Order By: Relevance
“…Transient transfection was performed as previously reported [17]. To test the transcriptional regulation of ZNF300 at the TRAF2 gene promoter, the expression vector pCDNA‐ZNF300 was co‐transfected into HeLa cells with pGL3‐TRAF2 or a luciferase reporter driven by a composite promoter containing three copies of the wild‐type NF‐κB responsive element (three times NF‐κB‐Luc) [34].…”
Section: Methodsmentioning
confidence: 99%
“…Transient transfection was performed as previously reported [17]. To test the transcriptional regulation of ZNF300 at the TRAF2 gene promoter, the expression vector pCDNA‐ZNF300 was co‐transfected into HeLa cells with pGL3‐TRAF2 or a luciferase reporter driven by a composite promoter containing three copies of the wild‐type NF‐κB responsive element (three times NF‐κB‐Luc) [34].…”
Section: Methodsmentioning
confidence: 99%
“…That study also showed that ZNF300 has the same binding affinity to the DNA sequences CTGGGGGCG and ACGGGGGCG [10]. Further EMSA was carried out to detect whether changing the first nucleotide (an A → G, C or T change) of ACGGGGGCG would affect the binding affinity of ZNF300 to this consensus.…”
Section: Resultsmentioning
confidence: 77%
“…Recombinant ZNF300 and Egr1 share binding sites in vitro In our previous study, we found that ZNF300 binds specifically to a GC-rich element (C(t/a)GGGGG(g/c)G) through its zinc finger domains [10]. That study also showed that ZNF300 has the same binding affinity to the DNA sequences CTGGGGGCG and ACGGGGGCG [10].…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations